Competency‐Based Assessment Tool for Pediatric Esophagoscopy: International Modified Delphi Consensus. (9th October 2020) - Faucett, Erynne A.; Wolter, Nikolaus E.; Balakrishnan, Karthik; Ishman, Stacey L.; Mehta, Deepak; Parikh, Sanjay; Nguyen, Lily H. P.; Preciado, Diego; Rutter, Michael J.; Prager, Jeremy D.; Green, Glenn E.; Pransky, Seth M.; et al.
Abstract : Objectives/Hypothesis: Create a competency‐based assessment tool for pediatric esophagoscopy with foreign body removal. Study Design: Blinded modified Delphi consensus process. Setting: Tertiary care center. Methods: A list of 25 potential items was sent via the Research Electronic Data Capture database to 66 expert surgeons who perform pediatric esophagoscopy. In the first round, items were rated as "keep" or "remove" and comments were incorporated. In the second round, experts rated the importance of each item on a seven‐point Likert scale. Consensus was determined with a goal of 7 to 25 final items. Results: The response rate was 38/64 (59.4%) in the first round and returned questionnaires were 100% complete. Experts wanted to "keep" all items and 172 comments were incorporated. Twenty‐four task‐specific and 7 previously‐validated global rating items were distributed in the second round, and the response rate was 53/64 (82.8%) with questionnaires returned 97.5% complete. Of the task‐specific items, 9 reached consensus, 7 were near consensus, and 8 did not achieve consensus. For global rating items that were previously validated, 6 reached consensus and 1 was near consensus. Conclusions: It is possible to reach consensus about the important steps involved in rigid esophagoscopy with foreign body removal using a modified Delphi consensus technique. These items can now be considered when evaluating trainees during this procedure. This tool may allow trainees to focus on important steps of the procedure and help training programs standardize how trainees are evaluated. Level of Evidence: 5. Laryngoscope, 131:1168–1174, 2021